The N-Terminal Region of Cucumber Mosaic Virus 2a Protein Is Involved in the Systemic Infection in Brassica juncea - Tae-Seon Park; Dong-Joo Min; Ji-Soo Park; Jin-Sung Hong (Plants, 2024)
Brassica juncea belongs to the Brassicaceae family and is used as both an oilseed and vegetable crop. As only a few studies have reported on the cucumber mosaic virus (CMV) in B. juncea, we conducted this study to provide a basic understanding of the B. juncea and CMV interactions. B. juncea-infecting CMV (CMV-Co6) and non-infecting CMV (CMV-Rs1) were used. To identify the determinants of systemic infection in B. juncea, we first constructed infectious clones of CMV-Co6 and CMV-Rs1 and used them as pseudo-recombinants. RNA2 of CMV was identified as an important determinant in B. juncea because B. juncea were systemically infected with RNA2-containing pseudo-recombinants; CMV-Co6, R/6/R, and R/6/6 were systemically infected B. juncea. Subsequently, the amino acids of the 2a and 2b proteins were compared, and a chimeric clone was constructed. The chimeric virus R/6Rns/R6cp, containing the C-terminal region of the 2a protein of CMV-Rs1, still infects B. juncea. It is the 2a protein that determines the systemic CMV infection in B. juncea, suggesting that conserved 160G and 214A may play a role in systemic CMV infection in B. juncea.